Autogestión institucional en salud mental ante amenaza volcánica en la Universidad De Nariño - Mora Durán, Karen Andrea; Gallego Zamora, Amarantha; Ojeda Rosero, Dayra Elizabeth (Universidad y Salud, 2011)
In this article an action research process is described since the analysis and the mobilization of processes of risk management including attention in mental health, from a self-management institutional perspective towards an eventual eruption of the Galeras Volcano, from: 1) the dialogue and the participative construction with diverse actors from the university community and the region; 2) the identification of the characteristics and the types of vulnerability towards the volcanic hazard the community is exposed to; 3) the strengthening of actions orientated to reduce situations which produce risk, through self-management institutional processes. The methodology reflects a relation of collaboration among people from the university community represented by professors, researching groups from different areas, students and local and regional institutions which are in charge of the integrated risk management, facilitating spaces for the co-constructions of alternatives during the meetings. The research is based on a wide literature review about volcanic hazard and its effects over mental health, contextualized to the reality of the university community.